Pelaksanaan Izin Poligami di Pengadilan Agama Dumai Studi Kasus Perkara Nomor 001/Pdt.G/2013/PA.Dum - Nina Haryati; Mardalena Hanifah; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Marriage in Indonesia adheres to the principle of monogamy. Where a husband has only one wife as well as a wife just had a husband. Polygamy is one of the problems in the marriage of the most widely discussed and controversial. Polygamy should be done but must be in accordance with applicable law that is in accordance with Article 4 of the Marriage Act. In fact there are those who apply to the Court Religion is not in accordance with the applicable legislation.The formulation of the problem is taken, first, whether the reasons for the submission of permit polygamy in the Religious Dumai? Secondly, How consideration judge in case the decision No. 001 / Pdt.G / 2013 / PA.Dum? This study uses empirical juridical approach, data collection by using descriptive analysis, both primer and secondary, cases collected through observation, interviews and studies legal documents, while the technique of data analysis done qualitatively.In Article 4 paragraph (2) of the Law of Marriage reasons that can be submitted to the Islamic Court is not able to perform the duties of a wife as a wife; wife got a disability or illness can not be cured; A wife can not give birth to offspring. In the implementation of the Religious Court case dumai role in decision No. 001 / Pdt.G / 2013 / PA.Dum not in accordance with the applicable provisions where the rationale used was the candidate's second wife was pregnant first. The judge in consideration of using the principle of contra legem ie the authority of judges to deviate the written provisions that already exist. Based on the description above, the reasons for which the applicant submitted to the Religious Court that candidate two pregnant first wife, second wife of the candidate tumor disease, the wife (respondent) can not give offspring. Basic consideration of the judge in the decision No. 001 / Pdt.G / 2013 / PA.Dum not in accordance with the legislation in force.Keywords : Marriage - License Polygamy - PA Dumai